2017
DOI: 10.1093/jat/bkx054
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Evaluation of Electronic Cigarettes: Multicomponent Analysis of Liquid Refills and their Corresponding Aerosols

Abstract: Electronic cigarette use has raised concern worldwide regarding potential health risks and its position in tobacco cessation strategies. As part of any toxicity assessment, the chemical characterization of e-liquids and their related vapors are among fundamental data to be determined. Considering the lack of available reference methods, we developed and validated several analytical procedures in order to conduct a multicomponent analysis of six e-liquid refills and their resultant vapor emissions (generated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 34 publications
6
81
1
Order By: Relevance
“…For studies reporting data in the form of plots (Mikheev et al 2016;Williams et al 2015), we used automated software tools to infer the underlying mean (SD) values [Origin (version 9.0; OriginLab Corporation)]. For studies that reported metal/metalloid levels for individual samples but not the mean (SD) (Beauval et al 2016(Beauval et al , 2017, we calculated the mean (SD). If metal/metalloid levels were below the limit of detection (LOD) and the study reported the original data but not the mean (SD), we replaced values below the LOD by LOD= p 2 before calculating the mean (SD) (Beauval et al 2016(Beauval et al , 2017Kamilari et al 2018;Margham et al 2016;Song et al 2018;Tayyarah and Long 2014).…”
Section: Metal/metalloid Data Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…For studies reporting data in the form of plots (Mikheev et al 2016;Williams et al 2015), we used automated software tools to infer the underlying mean (SD) values [Origin (version 9.0; OriginLab Corporation)]. For studies that reported metal/metalloid levels for individual samples but not the mean (SD) (Beauval et al 2016(Beauval et al , 2017, we calculated the mean (SD). If metal/metalloid levels were below the limit of detection (LOD) and the study reported the original data but not the mean (SD), we replaced values below the LOD by LOD= p 2 before calculating the mean (SD) (Beauval et al 2016(Beauval et al , 2017Kamilari et al 2018;Margham et al 2016;Song et al 2018;Tayyarah and Long 2014).…”
Section: Metal/metalloid Data Synthesismentioning
confidence: 99%
“…For studies that reported metal/metalloid levels for individual samples but not the mean (SD) (Beauval et al 2016(Beauval et al , 2017, we calculated the mean (SD). If metal/metalloid levels were below the limit of detection (LOD) and the study reported the original data but not the mean (SD), we replaced values below the LOD by LOD= p 2 before calculating the mean (SD) (Beauval et al 2016(Beauval et al , 2017Kamilari et al 2018;Margham et al 2016;Song et al 2018;Tayyarah and Long 2014). For studies reporting the mean (SD) for multiple groups (e.g., by nicotine levels, by different flavors) (Goniewicz et al 2014;Kamilari et al 2018;Talio et al 2015Talio et al , 2017Tayyarah and Long 2014), we calculated the weighted mean and total SD to facilitate summary and comparison across studies and device types after confirming there were no major differences across flavors and nicotine levels.…”
Section: Metal/metalloid Data Synthesismentioning
confidence: 99%
See 3 more Smart Citations